Experimental models for hepatitis C virus (HCV): New opportunities for combating hepatitis C - Trujillo Murillo, Karina del Carmen; Garza Rodríguez, María de Lourdes; Martínez Rodríguez, Herminia Guadalupe; Barrera Saldaña, Hugo Alberto; Bosques Padilla, Francisco Javier; Ramos Jiménez, Javier; Rivas Estilla, Ana María (2004)
Infection with hepatitis C virus (HCV) is a global public health issue. More than 200 million people in the world are infected with HCV. Hepatitis C is considered one of the main causes of chronic hepatitis, cirrhosis, hepatocellular carcinoma and liver transplantation. The identification of the viral genome quickly allowed delineation of genomic organization, and the structure and biochemical characterization of the proteins of HCV. However, it has been difficult to study its life cycle, as well as the development of antiviral agents due to the lack of a system of permissible culture. Numerous attempts have been reported to establish an in vitro system for the study of HCV. Recently, a system of efficient culture was established that allows replication of subgenomic molecules of HCV in a cell line of human hepatoma. In this revision, after a brief description of the molecular biology, means of transmission and clinical characteristics of hepatitis C, some of the experimental models are described that have been developed to date, focusing mainly on the subgenomic replicon system and their use in the development of new antiviral treatments.